31.C. Workshop: Development and implementation of action plans on health literacy. (30th September 2020) - ,; ,
Abstract: Health literacy (HL) has become an important topic in many countries. As HL - meaning the ability to access, understand, appraise and apply health information (Sørensen et al. 2012) - is important to make sound health decisions, to promote health and to take an active part in managing health and illness in everyday life and navigating the health care system. In the modern digital knowledge society, HL is also indispensable for orienting oneself in the abundance of mostly digital health information, including incorrect and false information, for locating reliable information and for assessing the trustworthiness and quality of information. However, available studies show that HL is insufficient in many countries. Low HL has - as many studies show - negative social consequences ranging from unhealthy behaviour, higher risk for diseases, less self-care and deficits in coping with illness and chronicity, to over- and misuse (extensive use) of health care. The promotion of HL is therefore an important public health task. An increasing number of population studies and policy documents currently underline this. The WHO has therefore included HL into many of its strategies, like the declarations of Shanghai (2016) and Astana (2018), and has published several publications focusing on HL, like the Solid Facts (2013), the 57th Health Evidence Network Report (2018) or the Roadmap for Implementing Health Literacy Activities (2019). In many countries, strategies and national action plans to improve HL have been developed in response to the political call for action, e.g. in Scotland, Germany and recently also in Portugal. Other countries and regions are currently working on the development of a HL action plan, e.g. Belgium and the WHO European Region action plan on HL. The development and especially the implementation strategies of action plans in different countries and the experiences gained will be discussed comparatively in the workshop. Following an introduction (10'), two countries, which already have action plans will introduce their implementation strategy in one presentation each: Germany and Portugal (30'). This will be followed by two presentations of countries/regions in which action plans are currently being developed: Belgium and WHO Europe (30'). Afterwards the participants will have the opportunity to ask questions and discuss on the different strategies (20'). The workshop will help other initiatives to successfully develop and implement policy plans and strategies in different fields of public health. Key messages: Strategies and national action plans to improve HL have been developed in different countries/regions. It is important to reflect on the chosen development and implementation strategies and to discuss their effects, successes and barriers.